A Study of the Academic Leadership of Primary Education Administrators under the Chanthaburi Primary Educational Service Area Office 2 - สิงหกุล, อาภาภรณ์; การีเวท, สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of this research were: 1) to study the level of instructional leadership of school administrators under Chanthaburi Primary Educational Service Area Office 2; 2) to compare the instructional leadership of school administrators classified by gender, educational background, work experience, and school size; and 3) to study the guidelines for developing instructional leadership of school administrators. The sample consisted of 291 teachers in schools under Chanthaburi Primary Educational Service Area Office 2 in the 2025 academic year. The sample was obtained through stratified random sampling using the districts where the schools were located as strata, and simple random sampling by lottery. The research instruments were a questionnaire and an interview form. Data were analyzed using mean, standard deviation, t-test, One-way ANOVA, and content analysis.           The results revealed that:• The overall level of instructional leadership of school administrators under Chanthaburi Primary Educational Service Area Office 2 was at the highest level. When considered by each aspect, all aspects were also at the highest level. The aspect with the highest mean was monitoring student progress, followed by professional development, instructional supervision, and defining the school’s vision, goals, and mission, respectively.• The comparison of instructional leadership classified by teachers’ gender revealed statistically significant differences at the .05 level in overall, particularly in instructional supervision and monitoring student progress. However, no statistically significant differences were found when classified by educational background, work experience, or school size, either overall or by dimension.          3. The guidelines for developing instructional leadership of school administrators proposed that the administrators should determine academic vision, goals and mission by adhering all-sectors participation together with creating an atmosphere to support learning, promoting cooperation, transparency and sharing decision-making among teachers and stakeholders. Besides, the administrators should develop positive supervision, be good friends, give counsel, use technology to support supervision and promote systematic and continuous professional development of teachers and also apply assessment results as a data-based to improve instructional practices.